Teaching LGBTQ+ history in high schools - Berman, Stacie Brensilver, author. Link
1 online resource
Keywords: "Teaching LGBTQ+ History: Practical Strategies and Voices of Experience offers insights, concrete strategies, and lesson plans for teaching LGBTQ+ history in high schools. With essays from educators, historians, and activists, it speaks to the power and significance of LGBTQ+-inclusive curriculum and its greater necessity at a time when the LGBTQ+ community is both more visible and increasingly targeted. Across the US, challenges exist that prevent teaching LGBTQ+ history, including curriculum censorship laws prohibiting discussion of the LGBTQ+ community in schools. However, there are also grassroots movements in the US that are generating quality LGBTQ+ history curriculum and implementing them in secondary schools. This book shows how integrating LGBTQ+ content offers myriad benefits for all students, including making history more relevant and representative, and reversing years of silence and erasure in the sources, topics, and narratives that students encounter throughout their education. Combining insights from changemakers with practical strategies and lesson plans for teaching LGBTQ+ history, this book will equip educators with the rationale and resources they need to effectively integrate this history into the curriculum. It will also be highly valuable for pre-service teachers, particularly within Social Studies Education and Social Justice Education"--